Pengaruh Stres Kerja Dan Beban Kerja Terhadap Kinerja Pegawai Melalui Kepuasan Kerja Sebagai Variabel Intervening Pada Dinas Lingkungnan Hidup Kabupaten Agam - M Rahit Andriano; Robby Dharma; Omia Crefioza (CV. ITTC INDONESIA, 2026)
This study aims to analyze the effect of work stress and workload on employee performance, with job satisfaction as an intervening variable at the Environmental Agency of Agam Regency. Employee performance is an important factor in supporting the success of public sector organizations, particularly in delivering services to the community. This research employs a quantitative approach using a survey method. The population of this study consists of all employees of the Environmental Agency of Agam Regency, totaling 65 employees; therefore, the sampling technique used is the census method, in which the entire population is included as the research sample. Data were collected through the distribution of questionnaires developed based on the indicators of work stress, workload, job satisfaction, and employee performance variables. The collected data were then analyzed using the Structural Equation Modeling (SEM) technique with the Partial Least Squares (PLS) approach version 3. The results of the study indicate that work stress and workload have a significant effect on job satisfaction. In addition, work stress and workload also have a significant effect on employee performance. Job satisfaction is proven to have a significant effect on employee performance and is able to mediate the effect of work stress and workload on employee performance. These findings indicate that the level of job satisfaction plays an important role in strengthening or weakening the influence of work stress and workload on employee performance. Based on these results, it is recommended that the Environmental Agency of Agam Regency pay greater attention to managing employee stress and workload through proportional task distribution, increased organizational support, and the creation of a conducive work environment in order to sustainably improve job satisfaction and employee performance.